Prediction of Heavy Metals Values for South-East of Baghdad Study Area - Eman Abdul Rahman; Muthaina Abdullah Mustafa (Journal of Techniques)
Soil, water and air are the main components of the environment. The presence of old and modern factories that emit pollutant materials such as steam and smoke polluting the air and soil, as well as dumping solid and liquid wastes for these industries on the lands and in the adjacent water channels, and all these pollutants will negatively affect the environment surrounding the industrial sites. The factories are located south-east of the capital, Baghdad. This study aims to estimate the damage and seriousness of heavy metals pollution in the soil surrounding these factories. Soil samples are taken at three depths (0-10) (10-30) (30-50) cm with nine different sites. The necessary tests are carried out to find the concentrations of heavy metals such as copper (Cu), iron (Fe), cadmium (Cd), nickel (Ni), zinc (Zn), and lead (Pb), as well as phosphate (PO4) and PH. These tests values can be used in statistical program to obtain the analysis of variance tables for a significant level less than 0.05 in f-test. The least square difference method is used to find the significant difference among tests in one layer. The results show that, the second layer of soil is the worst where Mean square error is 24.432 with Mean Absolut error is 1.164 and Mean Absolut percentage error is 96.21. Using Minitab program to predict heavy metal values for the second layer and these values are not exceeding the permissible limits. In this study, the concentrations of heavy metals for the second layer of soil and for the nine sites starting from the first site are as follows Pb (3.05-11) mg/kg prediction values to Pb (3.15-17.35) mg/kg. Concentration of Cd (0.05-0.2) mg/kg while prediction values of Cd (0.09-0.31) mg/kg. Concentrations of Ni in second layer of soil (3-35) mg/kg; Prediction values Ni (4.41-37.08) mg/kg. Zn concentrations (0.6-22.5) mg/kg; Prediction concentration Zn (0.9-24.1) mg/kg. Concentrations Cu (0.35-8.55) mg/kg while predictions Cu (0.62-10.21) mg/kg. Concentrations of Fe (2.8-7.1) mg/kg. Prediction concentrations Fe (3.61-9.22) mg/kg. The benefits of prediction concentration of heavy metals in soil is crucial to finding solutions to contaminated soil in simple ways with primary treatment and acceptable measures for recycle waste factories. Loss of food security in the event of aggravated soil contamination with heavy metals.